Mirizzi syndrome: diagnosis and management of a challenging biliary disease (BIRDEM Medical Journal, 2019)
Background: Mirizzi syndrome is a condition, difficult to diagnose pre-operatively and treat, represent a particular challenge for hepatobiliary surgeons. Furthermore, it increases the risk of intra-operative biliary injury, particularly during laparoscopic cholecystectomy. The aims of this study were to point out some particular aspect of diagnosis and treatment of this condition that will be helpful for the surgeons.Methods: We retrospectively reviewed all records of the patients, surgically treated for Mirizzi syndrome from January 2013 to January 2018 in Dhaka Medical College Hospital, Shaheed Sohrawardy Medical College Hospital and BIRDEM General Hospital. Patients’ presentation, diagnostic methods, treatment and complications were recorded.Results: During the study period, a total of 1320 cholecystectomy were performed, out of which 50 patients were diagnosed with Mirizzi syndrome, representing an incidence rate of 3.78%. Male to female ratio was 0.72:1 and mean age was 54.14 years. When we analyzed the main symptoms in the clinical debut, we found that common features were jaundice (31, 62%), cholangitis (20, 40%) and abdominal pain (22, 44%). Roux en Y hepaticojejunostomy was the treatment of choice and subtotal cholecystectomy were done for 7 cases and laparoscopic cholecystectomy for 2 cases. Mean hospital stay was 4.8±2.9 days. There was no post-operative mortality. Two cases of biliary fistula resolved with conservative management and another case required percutaneous treatment for resolution of an intraperitoneal postoperative collection.Conclusion: Mirizzi syndrome continues to be a disease of difficult diagnosis and treatment. General surgeons without long experience in hepatobiliary surgery should refer the patient to a specialized hepatobiliary surgical center. In most of the cases biliary reconstruction is inevitable. It is important for the surgeons to know the disease and possible intra-operative challenging situations.Birdem Med J 2020; 10(1): 7-11